Respon Petani Bawang Merah Terhadap Model Pemberdayaan Masyarakat Di Kabupaten Majene - Dewi, Suryani; Fitri, Fitri; Amran, Arman (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The unused land in Pamboborang village, Banggae district, Majene district is now developing into red garlic farmland. For more than five years, garlic farmers have not achieved independence in business and tend to rely on of this study was to analyze the level of response of garlic farmers to empowerment models and to identify empowering models that match the need to encourage farmers' self-reliance. The research was conducted in Pamboborang Village, Majene Regency. Respondents were selected purposefully as many as 30 farmers. The data analysis used was a Likert scale with a qualitative descriptive method. The results showed that the response parameters of farmers were divided into four namely perception, attitude, skills and motivation. The four parameters produce a moderate response. The empowerment model that has been received by farmers is the model of extension and the support of agricultural production facilities and infrastructure (charity), while the empowerment model that is urgently needed by farmers is training (87.5%) and sustainable assistance (68.96%). The research serves as the basis for a study to develop a community empowerment model that can be carried out by stakeholders to increase the capacity of farmers in realising farmer self-reliance and food self-sufficiency in Majene District.